2008
DOI: 10.1111/j.1550-7408.2008.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Mechanisms of the Secondary Metabolite Euplotin C: Signaling and Functional Role in Euplotes

Abstract: Among secondary metabolites, the acetylated hemiacetal sesquiterpene euplotin C has been isolated from the marine, ciliated protist Euplotes crassus, and provides an effective mechanism for reducing populations of potential competitors through its cytotoxic properties. However, intracellular signaling mechanisms and their functional correlates mediating the ecological role of euplotin C are largely unknown. We report here that, in E. vannus (an Euplotes morphospecies that does not produce euplotin C and shares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Many natural marine products function as chemical weapons and have evolved into highly potent inhibitors of physiological processes in prey, predators, or competitors of the marine organisms that produce them (Haefner 2003). A good example of this is the secondary metabolite euplotin C, which is produced by the ciliated protist E. crassus , providing an effective mechanism for damping populations of potential competitors, thus favoring the entrance into new niches and, more generally, the adaptative radiation of this producer species (Dini et al 1993; Guella et al 1994, 1996; Savoia et al 2004; Trielli et al 2008). In this line, competition experiments performed in mixed cultures of producer E. crassus , non‐producer, sensitive E. vannus , and non‐producer, sensitive Euplotes minuta indicated that the producers have a growth advantage over non‐producers (Dini et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural marine products function as chemical weapons and have evolved into highly potent inhibitors of physiological processes in prey, predators, or competitors of the marine organisms that produce them (Haefner 2003). A good example of this is the secondary metabolite euplotin C, which is produced by the ciliated protist E. crassus , providing an effective mechanism for damping populations of potential competitors, thus favoring the entrance into new niches and, more generally, the adaptative radiation of this producer species (Dini et al 1993; Guella et al 1994, 1996; Savoia et al 2004; Trielli et al 2008). In this line, competition experiments performed in mixed cultures of producer E. crassus , non‐producer, sensitive E. vannus , and non‐producer, sensitive Euplotes minuta indicated that the producers have a growth advantage over non‐producers (Dini et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These events parallel the disassembling of the ciliary structures, the inhibition of cell motility, the occurrence of aberrant cytoplasmic vacuoles, and the rapid inhibition of phagocytic activity. Euplotin C also increases lysosomal pH and decreases lysosomal membrane stability of E. vannus (Trielli et al 2008). Nevertheless, the cytotoxic properties of euplotin C in E. vannus have not been clarified and possible involvement of euplotin C‐induced PCD is currently unknown in E. vannus in particular and in protists, in general.…”
mentioning
confidence: 99%
“…3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay Cell viability was assessed by the reduction of MTT, as previously described [22][23][24][25]. Jurkat or U-373 cells were seeded in 96-well plates at a density of 2.5 Â 10 5 cells/ml, before treatments.…”
Section: Methodsmentioning
confidence: 99%
“…, intracellular Ca 2+ concentration, organelle components and related caspases [46]. The most important and general outcome of this study is that the chemical signal carried by euplotin is transduced in a rapid impairing of the membrane electrical properties.…”
Section: Terpenoids From Euplotes Crassusmentioning
confidence: 99%
“…Furthermore, these terpenoids display activities against other ciliates, competing for space and resources, and also possess interesting biological properties such as apoptotic activity towards mouse and rat tumor cell lines [29,45]. Generally, the lipophilic nature of these compounds indicates that their principal targets are likely to be cell membranes, wherein they could play a role in chemioosmotic control [46]. Moreover, there is evidence from bioassays that terpenoids are non-covalently bound to the ciliate’s external membrane.…”
Section: Functional Role and Phylogenetic Significancementioning
confidence: 99%